HIGH SCHOOL AS A BOARD GENERAL SERVICES (BLU) IN ADVANCE THE WORLD OF EDUCATION IN INDONESIA - Idawati Idawati (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to explain how the vision of Indonesian state universities in preparing educational and non-educational personnel by paying attention to the quality and relevance of effectiveness, developing and disseminating knowledge and seeking its use in order to improve people's living standards and enrich national culture. This type of research is a qualitative research with a phenomenological approach. Sources of field data are in the form of primary data and secondary data. Collecting research data using observation techniques, interviews and document studies. Data analysis techniques consist of data collection, data reduction, data presentation, and conclusions. The data validity techniques consist of credibility, transferability, dependability, and confirmability. The conclusion in this study is that tertiary institutions are educational units at the higher education level that carry out the tridharma of higher education in the form of education and teaching, research, and community service. Universities that are meant are academics, polytechnics, high schools, institutes, and universities. Higher education as a public service agency is a government institution whose management is carried out with the principles of efficiency and productivity.Keywords: Higher Education, BLU, Education.